KONTESTASI KELIAN ADAT DALAM PEMILUKADA SERENTAK DI KOTA DENPASAR TAHUN 2015 - Radha, Ni Putu Whraspati; Azhar, Muhammad Ali; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2017)
ABSTRAC T Contestation of Kelian Adat in the General Election in Denpasar in 2015, became an interesting subject of research by explaining the position of the Kelian Adat as a bridge to facilitate political activity that touches Banjar Adat. Reduced public confidence in the political parties, to make the political parties are not the only supporters of victory. Kelian Adat as Banjar Adat leaders have an important role in mobilizing the masses. So one way to expand the domination of the Kelian Adat is used to facilitate the achievement of political objectives. The purpose of this study was to determine and describe the Contestation of Kelian Adat in the General Election in Denpasar in 2015. The theory used political elite theory. The method used in this research is descriptive qualitative method, while the technique of collecting data through observation, interview and documents. The results of this study found that, in the election Kelian Adat give major influence on the voting results of candidates. Given the way to condition the award of a pair of candidates raises a strategy known as suryak siu or briuk siu, where this condition is togetherness Balinese people in taking an action and should be uniform with no difference. In this study concluded that the contestation of Kelian Adat made in the implementation of the election simultaneously in Denpasar in 2015 with the Kelian Adat competing to bring in uniformity of manners Banjar voters. Keywords: Contestation, Kelian Adat, Unison Election 2015